Valor de empresas e medidas de desempenho econômico: um estudo em empresas atacadistas brasileiras - Miranda, Gilberto José (2005)
The present study has as main objective to verify which the concepts and methodologies of measurement of economical acting have been used in Brazilian wholesale companies, that can contribute to the adoption of models based in the value. Considering that the approaches of the Residual Economical Result (RER), Discounted Cash flow (FCD) and Integral Economical Result (REI - GECON) they are methodologies that have potential to contribute with the Value Based Management (VBM), it was looked for to verify if the pertinent concepts to these methodologies have been implemented in practice. For so much, an empiric research was accomplished in 101 wholesale companies and Brazilian distributors. It was verified that the most generic concepts on the approach of the value are quite disseminated in those companies. However, when it breaks for the pragmatic use, this reality changes, because it was not identified a group of companies that used the approach of the value in the fullness. The one that it identified was the existence of companies with some appropriate instruments, and another using in a partial way the concepts requested on the part of the Value Based Management. It seems there to be an attempt of the companies in applying what is possible in agreement with the reality of each one of them. However, of course the traditional measures of acting (revenue, gross and operational margin, profit and return on the investment) still prevail in the researched atmosphere.